Korelasi Penguasaan Kosakata Arab dan Motivasi Belajar Terhadap Prestasi Menghafal Al-Qur’an Santri kelas VIII Mts Darul Qur’an Medan - Rahmadani,; Abidin, Munirul (Shaut al Arabiyyah, 2025)
The purpose of this study is to measure the relationship between vocabulary mastery and learning motivation on the achievement of memorizing the Quran. This study uses a Quantitative approach with a correlational type of research. The population in this study were all 8th grade students of MTS Darul Quran Medan, totaling 20 people. The data collection technique used in this study is a questionnaire. The data that has been collected is then analyzed by Pearson validity test, reliability test, Multiple Linear Regression analysis through the SPSS version 25 statistical program. The results showed that there is a significant relationship between mastery of Arabic vocabulary and learning motivation on the achievement of memorizing the Quran, so it can be concluded that there is a strong and positive relationship between mastery of Arabic vocabulary and learning motivation on the achievement of memorizing the Quran. Evidenced by the value of the hypothesis test results which is 0.001, which is smaller than 0.05 and the R square value is 78.4%. Thus, the results of this study confirm the importance of mastery of Arabic vocabulary and learning motivation in improving the achievement of memorizing the Al-Qur’an, and these two factors are some of the factors that must be prioritized in memorizing the Al-Qur’an.